Targeting the melanoma-associated antigen CSPG4 with HLA-C*07:01-restricted T-cell receptors - Kropp, Korbinian N.; Fatho, Martina; Huduti, Enes; Faust, Marilena; Lübcke, Silke; Lennerz, Volker; Paschen, Annette; Theobald, Matthias; Wölfel, Thomas; Wölfel, Catherine (Frontiers in Immunology, 2023)
Intorduction Chondroitin sulfate proteoglycan 4 (CSPG4), also known as high molecular weight-melanoma associated antigen, is expressed in melanoma but also other tumor entities and constitutes an attractive target for immunotherapeutic approaches. While recent preclinical reports focused on anti-CSPG4 chimeric antigen receptors (CAR), we here explore T-cell receptor (TCR)-based approaches targeting CSPG4. Methods The TCRs of two CSPG4-reactive T-cell clones (11C/73 and 2C/165) restricted by the highly prevalent HLA-C*07:01 allele were isolated and the respective αβTCR pairs were retrovirally expressed in CRISPR/Cas9-edited TCR-knockout T cells for functional testing. We also combined alpha and beta TCR chains derived from 11C/73 and 2C/165 in a cross-over fashion to assess for hemichain dominance. CSPG4+ melanoma, glioblastoma and lung cancer cell lines were identified and, if negative, retrovirally transduced with HLA-C*07:01. Results Functional tests confirmed specific recognition of CSPG4+HLA-C*07:01+ target cells by the αβTCR retrieved from the parental T-cell clones and in part also by the cross-over TCR construct 2Cα-11Cβ. Despite high surface expression, the 11Cα-2Cβ combination, however, was not functional. Discussion Collectively, 11C/73- and 2C/165-expressing T cells specifically and efficiently recognized CSPG4+HLA-C*07:01+ cancer cells which warrants further preclinical and clinical evaluation of these TCRs.